THE EFFECT OF LEARNING ORGANIZATION AND ORGANIZATIONAL CULTURE ON THE COMMITMENT OF BANTEN PROVINCE LPMP PERSONNEL - Bahdeur Maulana; Matin Matin; Heru Heru (International Journal of Education, Information Technology, and Others, 2019)
The purpose of this research is to see the influence of (1) learning organization, (2) organizational culture, (3) commitment of LPMP Banten Province employees. This research uses an associative quantitative approach with survey methods and correlational techniques. The survey was conducted from August to October 2018, involving 75 LPMP Banten Province employees with ASN status. Determination of the research sample is done by themethod Purposive Sampling. The findings of this research indicate first, a meaningful positive relationship between Learning Organizations and employee commitment. This means that the higher the Learning Organization, the higher the employee commitment. In other words, high employee commitment can be created by improving Learning Organization a better. Second, there is a significant positive relationship between organizational culture and employee commitment. This means that high employee commitment can be created by improving building a good organizational culture. Third, there is a significant positive relationship between learning organizationsorganizational andculture together with employee commitment. This means that the higher the learning organizationorganizational andculture, the higher the employee commitment.